Alpha-amylase Activity in Serum is Positively Associated with C-reactive Protein in Obesity and Diabetes - Rahman, Md Atiqur; Ripon, Md Abdur Rahman; Amin, Mohammad Tohidul; Bhowmik, Dipty Rani; Bhuiyan , Md Shafiullah; Hossain, Mohammad Salim (Dhaka University Journal of Pharmaceutical Sciences, 2024)
Alpha-amylase plays a critical job in metabolic homeostasis. Appraisal of alpha-amylase activity in metabolic disorders, for example, obesity and diabetes are important. The current investigation was meant to evaluate the relationship of alpha-amylase activity with C-reactive protein in obesity and diabetes. Alpha-amylase activity along with different biochemical markers like glucose level, triglyceride, total cholesterol, C-responsive protein, and creatinine level were analyzed in healthy, obese, and diabetes populations. In obese and diabetes, a significant deviation (p<0.05) was seen in the degree of biochemical markers including blood glucose, lipid profile, C-reactive protein (CRP), creatinine, and alpha-amylase action when compared with healthy volunteers. The alpha-amylase activity was found to be strongly associated (p< 0.01) with Body Mass Index (BMI), blood glucose level, and duration of diabetes Thus, it can be stated that alpha-amylase can initiate a cross-linking mechanism between BMI and blood glucose level facilitating the propensity of obesity and diabetes. Moreover, alpha-amylase indicated a positive correlation with CRP, a marker for inflammation, proposing a complex job in mediating inflammation in obesity (r= 0.486, p < 0.01) and diabetes (r=0.507, p<0.01). Serum creatinine was demonstrated as an insignificant positive correlation with alpha-amylase activity in obesity and type-2 diabetes. Alpha-amylase can be considered as a significant hazard factor in the pathogenesis of obesity and diabetes-related complications. Dhaka Univ. J. Pharm. Sci. 23(1): 7-12, 2024 (June)